Pengaruh Persepsi Tentang Pendidikan Dan Motivasi Belajar Siswa Terhadap Minat Melanjutkan Ke Perguruan Tinggi - Rahman, Rahman; H, Fendy Hariatama (Edunomics Journal, 2024)
The purpose of this study was to determine the effect of perceptions about education and student learning motivation on interest in continuing to college among students at SMAN 2 Palangka Raya. The research method used in this research is quantitative research method using descriptive approach. The source of data in this study were students of class XII IPS 1, 2, and 3 with a sample of 30 students. Based on the results of the study, it is known that the variable perception of education has a significant effect on the Interest in Continuing to College with the results obtained < 0.05 namely 0.000 < 0.05, and the value of t count> t table, namely 7.477 > 2.052, while the Learning Motivation variable has a significant effect on the Interest in Continuing to College, namely with the results obtained < 0.05, namely 0.008 < 0.05, and the value of t count> t table, namely 2.883> 2.052. Based on the value of the Coefficient of Determination, which is 0.802, meaning that the results above have an influence of variables XI and X2 on variable Y of 80.2%, and the remaining 19.8% is influenced by other factors outside the research that the researchers conducted